Comparison of feed efficiency rankings of heifers fed low and high energy dense diets - Christopher, J.A.; Marston, T.T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Concepts related to energy efficiency in cattle have been the basis for many research projects. Even though differences in individuals have long been recognized, little effort has been focused on the causes of the observed variations. The concept of residual feed intake was first introduced in 1963, and is calculated as the difference between actual feed intake by an animal and its expected feed intake based on body weight and growth rate. Residual feed intakes are phenotypically independent of the production traits used to calculate expected feed intake. Consequently, residual feed intake values can be useful in comparing individuals differing in level of production during a test period. These feed efficiency calculations have been shown to be a more accurate indicator of genetic variation in efficiency because they are independent of production traits. Thus, selection for improved residual feed intake makes it feasible to reduce feed intake without compromising growth performance. Hence, this trait could have great economic value to all segments of the beef industry. Energy density of cattle diets varies substantially and the selection for the ability to efficiently utilize high roughage diets does not guarantee efficient utilization of high grain diets. The objective of this study was to determine if energy density of the diet influences the ranking of cattle within a contemporary group and to determine if residual feed intake is influenced by changes in body composition and diet digestibility.
Keywords: Beef; Cattle; Energy efficiency